2013
DOI: 10.1007/s40141-012-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hemiplegic Shoulder Pain

Abstract: Stroke remains one of the leading causes of death in the United States. However, due to advancements in medical care, more and more Americans are surviving the acute event and living with disability of varying degrees. One factor that has been shown to decrease functional recovery and quality of life in this population is hemiplegic shoulder pain (HSP). Due to the diverse nature of possible etiologies, the exact cause of HSP in a patient is often obscure, thus making effective treatment equally as elusive. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Upper extremity spastic muscle overactivity has been identified as one of the most common causes of HSP and may appear in the acute phase (56). Regardless of the pathology, a review found that HSP is higher than normal in patients with PSS (57). HSP patients showed significantly more spasticity in affected limbs compared to limbs that are pain-free (58).…”
Section: Discussionmentioning
confidence: 99%
“…Upper extremity spastic muscle overactivity has been identified as one of the most common causes of HSP and may appear in the acute phase (56). Regardless of the pathology, a review found that HSP is higher than normal in patients with PSS (57). HSP patients showed significantly more spasticity in affected limbs compared to limbs that are pain-free (58).…”
Section: Discussionmentioning
confidence: 99%
“…As a cohort analysis, this study had no control arm, but we can compare our results with those in the published literature. Although there is an extensive literature on response rates to individual interventions (19) (1). These two studies showed a response rate of 14-27%.…”
Section: Discussionmentioning
confidence: 99%